(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Fatalities due to electrocution are unusual, and most of the cases are accidental in nature. They have not been studied earlier in the northern region of West Bengal. Objectives: The study was designed to find out the incidence and circumstances of death due to electrocution, with special emphasis on the patterns of injuries sustained by the victims. Methods: A retrospective study was carried out at the mortuary of the Department of Forensic Medicine and Toxicology at a tertiary care hospital of northern region of West Bengal. All the dead bodies brought for postmortem examinations during the period from January 1, 2022, to December 31, 2023, were analyzed. The detailed analysis of these cases was based on the inquest report, medical records, and the evaluation of autopsy reports. Results: A total of 32 cases of electrocution deaths were studied, in which males outnumbered females. The highest number of electrocution deaths were observed in the age groups of 21–30 years and 31–40 years, accounting for 25% each. Most of the victims were Hindus and occupied the agricultural sector. 56.25% of subjects were electrocuted at their homes, while 25% of cases died before reaching the hospitals. 87.5% of cases were electrocuted by low-voltage domestic supplies. In more than half of the cases, both entry and exit wounds were found, while only an entry wound was observed in 34.38% of cases. Conclusion: Although fatalities due to electrocution represent a small percentage of unnatural deaths, they could be prevented by increasing awareness regarding various safety measures among consumers.